(untitled) - Cortina, Joe (Boston, 2005)
Opening Doors is an intermediate college reading improvement text that presents a systematic way for students to approach their college reading assignments. Its 27 reading full-length reading selections from both textbooks and popular sources, plus 2 chapter-length selections allow opportunities for integrated, recursive practice of essential reading comprehension skills, critical reading skills, and study strategies. This new edition includes fuller explanations, enhanced illustrations and graphics, eight new reading selections, and expanded reading selection quizzes.
Keywords: College readers,Độc giả sinh viên